Timber and timber trees, native and foreign - Laslett, Thomas (Macmillan, 1894)
The author tackles his subject firstly in three sections: 'On Timber in General', 'The Timber of Dicotyledonous Tress' and 'Coniferous Timber Trees', followed by appendices on uses of timber, tensile and vertical strength, elasticity and transverse strength, and more.
Includes index.
Keywords: Forests and forestry.; Wood.; Timber.; elektronické knihy; electronic books